Juridical Analysis of 3 Kg LPG Distribution Supervision Policy by Local Government: A Case Study in Jambi Province - Syurpana Nofanda (International Journal of Law Society Services, 2025)
This study analyzes the 3 kg LPG distribution supervision policy in Jambi Province from a juridical perspective. The approach applied is normative juridical accompanied by literature analysis, which is supported by documentation studies as the main data collection method. The research findings indicate that the implementation of supervisory policies in Jambi Province has not been optimal due to several factors: (1) a weak distribution system that allows misappropriation practices such as sales above the HET (Highest Retail Price), hoarding, and adulteration; (2) limited coordination between relevant government agencies; (3) a lack of human resources and budget for supervision; (4) low public awareness; and (5) suboptimal utilization of technology in the monitoring system. The juridical analysis revealed that although the regulatory framework from the central to local levels is in place, implementation is constrained due to weak enforcement mechanisms and unclear division of authority. This study recommends strengthening cross-sectoral coordination, increasing the capacity of supervisors, implementing an integrated information system, strengthening community participation, and strict and consistent law enforcement in order to strengthen the effectiveness of supervision of 3kilogram LPG distribution in Jambi Province.